Evaluación de la capacidad de remoción de un compuesto farmacológicamente activo de interés en agua residual sintética mediante una tecnología no convencional para el tratamiento de aguas. (2021)
This project focused on evaluating the removal capacity of C. vulgaris microalgae in the presence of Diclofenac Sodium in synthetic wastewater as a culture medium, because of the great scientific interest that the so-called emerging pollutants have aroused in bodies of water in recent years, for this purpose the methodology used, part of a Bibliometric analysis of the Scopus database, from the results, obtained, were used as search criteria in the bibliographic review stage, which based the selection of technology and the pharmaceutically active compounds of interest.